2021
DOI: 10.3390/aerospace9010021
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of Multimissile Formation Based on an Adaptive SA-PSO Algorithm

Abstract: In an effort to maximize the combat effectiveness of multimissile groups, this paper proposes an adaptive simulated annealing–particle swarm optimization (SA-PSO) algorithm to enhance the design parameters of multimissile formations based on the concept of missile cooperative engagement. Firstly, considering actual battlefield circumstances, we establish an effectiveness evaluation index system for the cooperative engagement of missile formations based on the analytic hierarchy process (AHP). In doing so, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…If f(x i ) < f (P best.i ), then set P best.i = x i. If f (x i ) > f (P best.i ), utilizing the above-mentioned simulated annealing acceptance probability p i to apply the Metropolis criterion [27]. If the probability p i is greater than a random number within the range [0, 1], then the state P best.i is still accepted.…”
Section: Simulated Annealing Particle Swarm Optimizationmentioning
confidence: 99%
“…If f(x i ) < f (P best.i ), then set P best.i = x i. If f (x i ) > f (P best.i ), utilizing the above-mentioned simulated annealing acceptance probability p i to apply the Metropolis criterion [27]. If the probability p i is greater than a random number within the range [0, 1], then the state P best.i is still accepted.…”
Section: Simulated Annealing Particle Swarm Optimizationmentioning
confidence: 99%
“…Formation control of collaborative systems has been researched extensively in the literature. Typical approaches for formation control can be categorized as behavioral (Alfeo et al, 2019), leader–follower (Gong et al, 2022; Liu et al, 2022; Rosa, 2020), virtual structure (Zhou et al, 2018), and graph theory (Yan et al, 2022; Yuhang et al, 2022) based approaches. Behavioral approach requires that every action of UAV should correspond to every expected behavior of UAV, and it is defined by the weighted average of behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zha et al [12] successfully applied a genetic algorithm to the probability integral method for parameter inversion, demonstrating notable advantages in terms of accuracy and reliability. Subsequent investigations explored the use of the modular vector method [13][14][15], particle swarm algorithms [16][17][18][19], simulated annealing algorithms [20,21], and others [22][23][24][25][26][27] for parameter inversion within the probability integral method framework, all yielding highly satisfactory results. In a comparative analysis of parameter inversion outcomes using various intelligent algorithms, Han Mei et al [28] confirmed that, with an appropriate choice of initial exploration values, the modular vector method excels in accuracy and reliability when contrasted with other algorithms.…”
Section: Introductionmentioning
confidence: 99%